Association between non-adequate health literacy and cancer screening adherence: a meta-analysis. (30th September 2020) - Isonne, C; Baccolini, V; Salerno, C; Giffi, M; Migliara, G; Mazzalai, E; Turatto, F; Marzuillo, C; De Vito, C; Villari, P
Abstract: Objective: Individuals with non-adequate health literacy (NAHL) are more likely to have poor health outcomes and behaviors, including a limited use of preventive services. This study aimed at summarizing the evidence on the association between NAHL and adherence to cancer screening programs. Methods: PubMed, Scopus, and Web of Science were searched. Cross-sectional studies conducted in any country, published through January 2020 and quantifying the association between NAHL and cancer screening adherence, were included. An adapted Newcastle-Ottawa Scale was used to assess quality. Inverse-variance random-effects methods were used to produce pooled estimates: overall, by cancer and by HL tool. Results: Seventeen articles of heterogeneous quality were included in the systematic review and 45 analyses were combined. NAHL was found to negatively influence screening adherence in both the crude (n = 26) and adjusted (n = 19) pooled analyses, and the association was slightly stronger in the latter (OR = 0.70, 95%CI: 0.62-0.79 and aOR=0.66, 95%CI: 0.57-0.76, respectively). Moreover, NAHL was significantly associated with lower adherence in all the types of cancer screening investigated: breast cancer (n = 7), aOR=0.55, 95%CI: 0.38-0.78; cervical cancer (n = 4), aOR=0.63, 95%CI: 0.53-0.75; prostate cancer (n = 1), aOR=0.60, 95%CI: 0.36-0.99, and colorectal cancer (n = 7), aOR=0.85, 95%CI: 0.74-0.97. Lastly, tools measuring NAHL with reading comprehension/numeracy items yielded the strongest association with the outcome (n = 5, aOR= 0.53, 95%CI: 0.35-0.80), that was attenuated in tools with either self-reported comprehension items (n = 7, aOR=0.72, 95%CI: 0.65-0.80) or medical term recognition items (n = 7, aOR=0.74, 95%CI: 0.57-0.95). Conclusions: This study shows that NAHL may have a significant impact on adherence in all types of screening programs analysed, independently of the tools applied to measure it. Hence, it should be a useful focus for interventions to improve screening participation rates. Key messages: Non-adequate health literacy negatively influences cancer screening adherence. Efforts to promote the uptake of cancer screening programs should consider and address NAHL.